Performance evaluation of wavelet-based algorithm for printed circuit board (PCB) inspection [UTM journal article] - 363678 Zuwairie Ibrahim; Syed Abdul Rahman Al-Attas; Zulfakar Aspar; Rokhamsani Ghazali
PSZJBL